Interventions for Persisting Ductus Arteriosus in the Preterm Infant - Obladen, Michael; Koehne, Petra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Over the past few years a remarkably rapid evolution in the professional level of neonatology and in the survival of immature infants has been witnessed. Persisting ductus arteriosus is common in this population and is associated with impaired longterm outcome. Many uncertainties exist concerning indication, approach, best time, and side effects of necessary measurements and interventions to avoid later neurodevelopmental handicaps of the survivors. Experts in neonatology and pediatric cardiology give their opinion in this book. We are sure it will help to define the level of evidence and to develop standards of intervention for persisting ductus arteriosus in Europe. Adequate dealing with the ductus will become a challenge for every perinatal center.
Basics -- Developmental Anatomy of the Ductus Arteriosus -- Regulation of Smooth Muscle Contraction -- Prostaglandin Metabolism and Effects of Inhibitors -- Postnatal Circulatory Adaptation -- Epidemiology of Persisting Ductus in Preterm Infants -- Clinical Features -- Persisting Ductus Arteriosus and Respiratory Problems -- Influence on Mesenteric Perfusion and Necrotizing Enterocolitis -- Persisting Ductus Arteriosus and Intraventricular Hemorrhage -- Diagnostics -- Echocardiographic Assessment -- Cerebral Doppler Sonographic Measurements -- Interventions -- Therapeutic Options -- Surgical Closure -- Comparison of Indomethacin and Ibuprofen -- Indomethacin Effects and Side Effects -- Complications of Cyclooxygenase Inhibition in Preterm Infants -- Ibuprofen in Infants Below 28 Gestational Weeks -- Intravenous Ibuprofen: State of Registration -- Perspectives -- Summary and Perspectives.
Keywords: Medicine; Obstetrics; Maternal and child health services; Cardiology; Pediatrics; Pediatric surgery; Medicine & Public Health; Maternal and Child Health; Cardiology; Pediatrics; Pediatric Surgery; Obstetrics/Perinatology.; Electronic books